PRINCIPLES OF THE HEALTH APPROACH TO SPORTS ACTIVITIES FOR CHILDREN WITH LOCOMOTOR DISORDERS - Mnazhov Kuat Kuanishbaevich (Web of Journals Publishing, 2025)
The article is devoted to the differentiated regime of the training process and methods of rehabilitation for musculoskeletal disorders in young athletes by means of therapeutic physical training.
Keywords: Sport, rehabilitation, musculoskeletal apparatus, therapeutic physical culture, scoliosis, flatfoot.